Preparation method and application of nitrogen defect functionalized carbon nitride with high ECL efficiency

By using a nitrogen-defect-functionalized carbon nitride preparation method and controlling carrier dynamics, the problem of insufficient electrochemiluminescence intensity of carbon nitride materials was solved, achieving high efficiency and stability in electrochemiluminescence, and advancing the development of biosensing platforms.

CN120887380APending Publication Date: 2025-11-04SOUTHEAST UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510682394.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-17
Filing Date
2025-05-26
Publication Date
2025-11-04

AI Technical Summary

Technical Problem

Existing carbon nitride materials exhibit complex charge transfer pathways in water, resulting in insufficient electrochemiluminescence intensity and limiting their application in bioanalysis and clinical diagnostics.

Method used

By introducing nitrogen-deficient functionalized carbon nitride and calcining it with urea and KOH at high temperature, a specific ratio of nitrogen-deficient functionalized carbon nitride is formed, thereby regulating carrier dynamics to improve electrochemiluminescence efficiency.

Benefits of technology

High electrochemiluminescence efficiency of carbon nitride materials was achieved, improving detection sensitivity and making them suitable for large-scale production. They also exhibit excellent ECL strength and stability, advancing the construction of a visualized biosensing platform.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120887380A_ABST
    Figure CN120887380A_ABST
Patent Text Reader

Abstract

The invention discloses high-ECL-efficiency nitrogen defect functionalized carbon nitride and a preparation method and application thereof.The preparation method comprises the steps that a carbon nitride precursor is dissolved in an alkali reagent, dried and ground, and a uniformly-mixed sample is obtained; and calcining the mixed sample in an inert gas atmosphere to obtain the nitrogen defect functionalized carbon nitride. The nitrogen defect functionalized carbon nitride prepared by the preparation method is simple and convenient in preparation process, rich and easily available in raw material source, low in cost, simple in synthesis process and suitable for large-scale production, provides an important illuminant for an electrochemical luminescence sensor, has high ECL efficiency and stable ECL signals, and can be applied to the electrochemical luminescence sensor. Huge potential and application prospects are shown in the fields of biological analysis, clinical diagnosis and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of materials chemistry technology, specifically relating to a method for preparing and applying high ECL-efficiency nitrogen-deficient functionalized carbon nitride. Background Technology

[0002] ECL (Extracorporeal Cl-Cellular Analysis) is widely used in commercial immunoassays for clinical diagnosis due to its high sensitivity and low background noise. Generally, high-efficiency ECL (Extracorporeal Cl-Cellular Analysis)... ECL Emitters play a central role in the development of biosensors with superior sensitivity. Polymer carbon nitride (CN) is an emerging ECL luminescent material that has attracted widespread attention from researchers due to its excellent photophysical properties, inherent biocompatibility, superior quantum efficiency, and significant physicochemical stability. Carrier dynamics are central to carbon nitride ECLs and have a crucial impact on their ECL efficiency. However, the complex kinetic constraints involving interactions across different timescales in its charge transfer pathway lead to limitations in its Φ (potential velocity) in water. ECL The low efficiency of carbon nitride (Cnitride) limits its visualization and detection capabilities. Current reports mainly focus on improving Cnitride ECL efficiency through metal / non-metal doping to enhance carrier dynamics, thus limiting its widespread application in bioanalysis and clinical diagnostics.

[0003] Defect engineering has been shown to have a wide range of effects on carrier dynamics in fields such as photocatalysis and electrocatalysis. Therefore, using nitrogen defect functionalized carbon nitride to regulate carbon nitride carrier dynamics at the molecular level can preserve the inherent biocompatibility of the material and improve ECL efficiency, which is of great significance for the construction of a visualized biosensing platform. Summary of the Invention

[0004] The purpose of this invention is to address the problems existing in the prior art by providing a method for preparing high-ECL-efficiency nitrogen-deficient functionalized carbon nitride. The carbon nitride prepared by this invention enhances ECL efficiency, the preparation method is simple, and it is highly practical. It effectively solves the bottleneck of insufficient electrochemiluminescence intensity in traditional carbon nitride materials affecting detection sensitivity. Furthermore, this material has a high Φ... ECL It emphasizes its potential as a platform to advance the transformation of visualized biosensing architectures.

[0005] The preparation method and application of the high ECL-efficiency nitrogen-deficient functionalized carbon nitride are proposed.

[0006] Technical solution: To achieve the above objectives, the present invention provides a method for preparing high ECL-efficiency nitrogen-deficient functionalized carbon nitride, characterized by comprising the following steps:

[0007] (1) Dissolve the carbon nitride precursor in an alkaline reagent by stirring, evaporate and dry the resulting solution overnight, grind it, and obtain a uniformly mixed sample;

[0008] (2) The mixed sample was calcined in an inert gas atmosphere to obtain nitrogen-defect functionalized carbon nitride (NV). x -CN is the compound of formula (1).

[0009] The carbon nitride precursor is urea, and the alkaline reagent is KOH or NaOH.

[0010] The mass ratio of the carbon nitride precursor to the alkaline reagent is 5:0.002-0.02.

[0011] The mass ratio of the carbon nitride precursor to the alkaline reagent is 5:0.01-0.02.

[0012] Most preferably, the mass ratio of the carbon nitride precursor to the alkaline reagent is 5:0.01.

[0013] In step (2), the calcination is carried out at a heating rate of 1-5℃ / min at 500-600℃ for 3-5 hours.

[0014] The high ECL-efficiency nitrogen-defect functionalized carbon nitride prepared by the preparation method described in this invention.

[0015] Among them, the high ECL-efficiency nitrogen-deficient functionalized carbon nitride at 2200 cm⁻¹ -1 Asymmetric tensile vibrations of -C≡N were observed at the location.

[0016] The high ECL-efficiency nitrogen-deficient functionalized carbon nitride possesses N vacancies (N... 2C ).

[0017] The application of the high ECL-efficiency nitrogen-defect-functionalized carbon nitride described in this invention in the detection of electrochemiluminescence radiation signals and nitrite.

[0018] The specific application process is as follows: using a nitrogen-defect-functionalized carbon nitride-modified FTO electrode as the working electrode, a platinum wire electrode as the counter electrode, Ag / AgCl as the reference electrode, a phosphate buffer solution, and a KCl solution as the electrolyte; inserting the above electrodes into the buffer solution, performing electrochemiluminescence testing, and detecting the electrochemiluminescence radiation signal.

[0019] This invention provides a high ECL-efficiency nitrogen-deficient functionalized carbon nitride, the structure of which is shown in formula (1):

[0020]

[0021] This invention addresses the shortcomings of carbon nitride by improving carrier dynamics in multiple ways, thereby enhancing ECL efficiency. It provides a novel modification for improving the ECL efficiency of carbon nitride. The carbon nitride prepared by this invention is obtained by calcining urea and KOH in a specific mass ratio under a nitrogen atmosphere and high temperature. The preparation process is simple and convenient, using readily available and inexpensive raw materials, making it suitable for large-scale production. The carbon nitride prepared by this invention exhibits high ECL efficiency and a stable ECL signal, demonstrating significant potential and application prospects in fields such as bioanalysis and clinical diagnostics.

[0022] This invention is the first to use urea as a precursor to directly react with KOH in a specific ratio to obtain high ECL-efficiency nitrogen-deficient functionalized carbon nitride. The ratio of urea to KOH is crucial in this invention, and the resulting material is NV. 0.01 When the urea to KOH mass ratio is 5:0.01 during material preparation (-CN), it exhibits excellent high ECL efficiency. However, when this ratio changes slightly, such as to 5:0.02 or 5:0.005, the ECL efficiency significantly decreases. Furthermore, the method of this invention allows for a narrower range of defect adjustment through heat treatment, while the alkali-assisted method allows for more flexible and precise adjustment of the ratio, achieving higher ECL strength.

[0023] Beneficial effects: Compared with the prior art, the present invention has the following advantages:

[0024] 1. The method for preparing high ECL-efficiency nitrogen-deficient functionalized carbon nitride provided by the present invention uses urea as a precursor material and KOH as an auxiliary material, and is prepared by calcination in a tube furnace. The preparation process is simple, the raw materials are abundant and the cost is low, making it suitable for large-scale production.

[0025] 2. The high ECL efficiency nitrogen-defect functionalized carbon nitride provided by this invention has stronger ECL strength and better ECL stability compared with traditional carbon nitride synthesized only by urea.

[0026] 3. The high ECL-efficiency nitrogen-defect-functionalized carbon nitride prepared by this invention provides an important luminescent material for electrochemiluminescence sensors and has potential application value in the fields of biology and medical testing. Attached Figure Description

[0027] Figure 1 (a)CN, (b)NV 0.01 SEM image of CN; (c) Color changes of samples with different KOH doping concentrations (from left to right: CN, NV) 0.002 -CN、NV 0.005 -CN、NV 0.01 -CN and NV 0.02-CN).

[0028] Figure 2 Functionalized carbon nitride (NV) with different nitrogen defect concentrations in Example 1 x X-ray diffraction (XRD) patterns of carbon nitride (CN) and carbon nitride (CN).

[0029] Figure 3 Functionalized carbon nitride (NV) with different nitrogen defect concentrations in Example 1 x FT-IR spectra of carbon nitride (CN) and carbon nitrogen (CN).

[0030] Figure 4 Functionalized carbon nitride (NV) with different nitrogen defect concentrations in Example 1 x Solid-state reactions of -CN and carbon nitride (CN) 13 C-magic-angle rotation (MAS) NMR spectra.

[0031] Figure 5 Nitrogen-deficient functionalized carbon nitride (NV) in Example 1 0.01 High-resolution N1s(ac) and C1s(bd) XPS spectra of carbon nitride (CN) and carbon nitrogen (CN).

[0032] Figure 6 Functionalized carbon nitride (NV) with different nitrogen defect concentrations in Example 1 x Comparison of ECL intensity between -CN and carbon nitride (CN).

[0033] Figure 7 NV in Embodiment 1 of the present invention 0.01 Comparison of ECL intensity and visualization between CN / K2S2O8 and CN / K2S2O8 under cyclic voltammetry.

[0034] Figure 8 In Embodiment 1 of the present invention, (a) CN / K2S2O8 and (b) NV 0.01 ECL stability plot of -CN / K2S2O8.

[0035] Figure 9 (a)NO2 - For NV x -CN ECL quenching mechanism; (b) NO2 at different concentrations - ECL intensity response diagram of CN; (c) NO2 at different concentrations - For NV 0.01 -CN ECL intensity response plot; different colors represent the concentrations on the x-axis, "au" indicates arbitrary units; (d) using NV 0.01 -CN and CN NO2 - The calibration curve was detected. I0 and I represent the values ​​of NO2 added, respectively.- ECL intensity before and after. Error bars represent the standard error derived from five independent measurements; (e) containing different concentrations of NO2. - NV under quenching effect 0.01 -A photo of the CN photoelectrode ECL. Detailed Implementation

[0036] The present invention will be further described below with reference to the accompanying drawings and embodiments.

[0037] Unless otherwise specified, all materials and reagents used in the embodiments are commercially available.

[0038] Urea was purchased from Sigma-Aldrich, USA, product number U1250-5KG.

[0039] Ru(bpy)3Cl2 is ruthenium tripyridine chloride hexahydrate, CAS No.: 50525-27-4.

[0040] Example 1

[0041] High ECL-efficiency Nitrogen Defect Functionalized Carbon Nitride (NV) x The specific steps for preparing -CN are as follows:

[0042] 15g of urea was dissolved in a KOH aqueous solution (0.03g of KOH dissolved in 10mL of H2O). The resulting solution was then evaporated and dried overnight in an oven at 80℃. The solution was then ground in an agate mortar to obtain a homogeneous sample. The sample was placed in a boat and then placed in a tube furnace. Nitrogen gas was first passed through the furnace for 30 minutes to ensure a nitrogen atmosphere throughout. The furnace was then calcined at 550℃ for 4 hours at a heating rate of 3℃ / min to obtain nitrogen-deficient functionalized carbon nitride (NV). 0.01 -CN).

[0043] Comparative Example 1

[0044] 15g of urea was placed in an ark and placed in a tube furnace. Nitrogen gas was first passed through for 30 minutes to ensure that the entire tube furnace was in a nitrogen atmosphere. Then, the ark was calcined at 550℃ for 4 hours at a heating rate of 3℃ / min to obtain carbon nitride (CN).

[0045] Comparative Example 2

[0046] Comparative Example 2 uses a different preparation method than that in Example 1, replacing the amount of KOH with 0.006 g, 0.015 g, and 0.06 g, respectively, to obtain nitrogen-deficient functionalized carbon nitride (NV). 0.002 -CN, NV 0.005 -CN, and NV 0.02 -CN.

[0047] Experimental Example 1

[0048] The morphology of the materials prepared in Example 1 and Comparative Examples 1 and 2 was characterized.

[0049] like Figure 1 As shown, Comparative Example 1 ( Figure 1 a) The material exhibits a typical two-dimensional layered structure with high surface smoothness. The layers are tightly stacked through van der Waals forces and π-π interactions, forming blocky aggregates. In stark contrast, Example 1, which was modified through defect engineering, shows... Figure 1 b) The introduction of defects disrupts the layered order of the material, leading to lamellar fracture and the formation of abundant mesoporous structures. Simultaneously, surface roughness increases significantly, and edges exhibit an irregular serrated morphology. Notably, with the gradient increase of KOH doping concentration (Comparative Example 2), NV... x -CN samples showed a regular trend of increasing apparent color depth. Figure 1 c) This phenomenon may be closely related to defect-induced electronic structure modification and the evolution of light absorption properties.

[0050] The crystal structure order of the materials prepared in Example 1 and Comparative Example 1 was determined.

[0051] like Figure 2 As shown, the XRD pattern of Comparative Example 1 exhibits two typical characteristic diffraction peaks: the (100) plane diffraction peak at 13.0° corresponds to the planar structure formed by the periodic arrangement of in-plane tri-s-triazine units; the (002) plane diffraction peak at 27.4° originates from the ordered stacking structure between aromatic layers. It is noteworthy that in Example 1, as the KOH doping concentration in the precursor increases, the intensity of the (100) and (002) plane diffraction peaks shows a significant synergistic attenuation trend, indicating that the defect construction process simultaneously disrupts the in-plane periodic order and the integrity of the interlayer stacking. This phenomenon can be attributed to the competitive reaction between KOH and the triazine intermediate during thermal polymerization, leading to the reconstruction of some structural units and subsequently inducing lattice distortion. This structural evolution pattern corroborates the morphological fragmentation observed by SEM, jointly revealing the destructive effect of defects on the intrinsic order of CN crystals.

[0052] like Figure 3 As shown, the detailed chemical structures of NVx-CN prepared in Example 1 and Comparative Example 2, and CN prepared in Comparative Example 1, were investigated by Fourier transform infrared spectroscopy (FTIR). The FTIR spectra of all CNs were in the ranges of 800 and 1100-1700 cm⁻¹. -1 The nearby peaks are typically attributed to planar bending of the triazine or heptaazine ring and tensile vibration of the CN heterocycle, respectively. Notably, NV-CN exhibits peaks at 2200 cm⁻¹. -1Asymmetric tensile vibrations of -C≡N were observed at the site. This indicates that the introduction of KOH leads to the formation of some cyano groups.

[0053] like Figure 4 As shown, through solid-state 13 Magic-angle rotation (MAS) NMR measurements provided NV data prepared in Example 1 and Comparative Example 2. x Further insights into the -CN structure. The NMR spectra of both samples show two strong peaks at 158.4 and 168.5 ppm, corresponding to Cn and Cn, respectively. 3N (2) and C 2N-NHx (1) In the chemical shift of the heptaazine unit, two new peaks were observed at 118.3 ppm and 170.7 ppm, which can be attributed to the carbon atom (4) in the cyano group and the C atom (3) adjacent to the cyano group, which are weaker due to the low content of introduced defects. This result forms a complementary chain of evidence with the characteristic vibrational peaks of the cyano group detected by FTIR, together revealing the cyano functional group introduced by KOH and its positional characteristics.

[0054] To further investigate the effect of KOH treatment on the CN elemental composition, X-ray photoelectron spectroscopy (XPS) and organic elemental analysis (EA) were performed, as shown in Tables 1 and 2. The N / C and O / C atomic ratios of Comparative Example 1 and Example 1 were determined by the two methods. EA detected only trace amounts of oxygen, which ruled out the possibility of KOH treatment introducing oxygen-containing functional groups. The O1s peak in the XPS spectrum was likely due to oxygen-containing substances adsorbed on the surface. Both methods consistently indicate that the C / N atomic ratio increases regularly with increasing KOH doping concentration, confirming the introduction of nitrogen vacancies.

[0055] Table 1. Elemental content analysis of XPS

[0056]

[0057] Table 2 Elemental Content Analysis of EA

[0058]

[0059] Table 3 N 2C N 3C NH x and charging effect in CN and NV 0.01 -Proportion in CN

[0060]

[0061] like Figure 5As shown, to further confirm the type of introduced nitrogen vacancy, narrow-scan C1s and N1s XPS spectra of Example 1 and Comparative Example 1 were performed and unconvoluted into their components. All samples' C1s XPS spectra showed a peak at 288.3 eV, consistent with typical aromatic CN=C coordination within the CN framework; the peak at 284.9 eV belonged to anisotropic carbons (CC / C=C). The high-resolution N1s spectra could be unconvoluted into four peaks, at 398.7 eV (N... 2C ), 400.5eV (N 3C ), 401.4eV (N -Hx ) and 404.2 eV (charge effect or positive charge localization in heterocyclic rings). The N1S peaks of XPS were fractionated, and the area integral of each peak was calculated. 2C The relative content of the sites decreased with the KOH concentration gradient (Table 3), clearly pointing to N in the triazine unit. 2C The formation of vacancies.

[0062] Combined analysis of FTIR, NMR, EA, and XPS multispectral data revealed that KOH precursor doping selectively etches N in the triazine units through a competitive reaction during thermal polymerization. 2C The site simultaneously generates terminal cyano groups and nitrogen vacancy defects.

[0063] Experimental Example 2

[0064] The signal acquisition method for high ECL-efficiency nitrogen-defect-functionalized carbon nitride is as follows:

[0065] Electrode cleaning: Select a fluorine-doped tin oxide (FTO) electrode (12-14Ω / sq) with a specification of 1cm×5cm and clean it by ultrasonication for 15min in appropriate amounts of acetone, ethanol and ultrapure water. Finally, dry it with high-purity nitrogen gas for later use.

[0066] Preparation of carbon nitride photoelectrode: 50 mg of the material prepared in Comparative Examples 1-2 or Example 1 was added to 100 mL of acetone and ultrasonically dispersed (100 W, 25 °C) for 3 h to obtain relatively stable CN or NV. x -CN nanoparticle suspension. Then add 10 mL of CN or NV... x The deposition solution was obtained by uniformly mixing a CN nanoparticle suspension and 3 μL HI. Two 1×5 cm² areas were then prepared. 2 The FTO electrode was immersed in the deposition solution for 1 cm, and the FTO electrodes were placed parallel to each other at a distance of 1.5 cm. A voltage of 25 V was applied for 10 min for electrophoretic deposition to obtain CN / NV. x -CN electrode, tested after natural drying.

[0067] The prepared carbon nitride photoelectrode (CN / NV) xThe working electrode was a platinum wire, the counter electrode was a platinum wire, and the reference electrode was an Ag / AgCl (saturated KCl) electrode. The buffer solution was a commercially available phosphate buffer solution (pH 7.4). The electrochemiluminescence assay was performed in an aqueous solution containing K₂S₂O₈ (15 mM) as a co-reactant and KCl (0.1 M) as the electrolyte. Cyclic voltammetry was used for electrochemiluminescence detection, with an initial potential of 0 V, a termination potential of -1.5 V, and a scan rate of 100 mV / s. The photomultiplier tube voltage was set to 170 V, and the electrochemiluminescence radiation signal was detected.

[0068] like Figure 6 As shown, the intensity of nitrogen-deficient carbon nitride ECL exhibits a volcano-like relationship with the alkali reagent content, NV 0.01 -CN has the highest ECL strength, with a 700% improvement over the original CN's ECL, and is superior to NV. 0.005 -CN, and NV 0.02 -CN has increased by 100%.

[0069] like Figure 7 As shown, in NV 0.01 In the comparison chart of ECL intensity under cyclic voltammetry between -CN / K2S2O8 and CN / K2S2O8, NV 0.01 -CN / K2S2O8 exhibits a larger ECL intensity value and visible electrochemiluminescence.

[0070] like Figure 8 As shown in the comparison chart of ECL stability between NV-CN / K2S2O8 and CN / K2S2O8, NV-CN / K2S2O8 has a more stable ECL signal.

[0071] Furthermore, using Ru(bpy)3Cl2 as the reference luminescent material according to the above method, the ECL efficiency of NV-CN / K2S2O8 was calculated to be 1480 times that of Ru(bpy)3Cl2 / K2S2O8 as the reference.

[0072] Experimental Example 3

[0073] The following is a high-ECL-efficiency method for detecting nitrite using nitrogen-deficient functionalized carbon nitride:

[0074] Electrode cleaning: Select a fluorine-doped tin oxide (FTO) electrode (12-14Ω / sq) with a specification of 1cm×5cm and clean it by ultrasonication for 15min in appropriate amounts of acetone, ethanol and ultrapure water. Finally, dry it with high-purity nitrogen gas for later use.

[0075] Preparation of carbon nitride photoelectrode: 50 mg of the material prepared in Comparative Example 1 or Example 1 was added to 100 mL of acetone and ultrasonically dispersed (100 W, 25 °C) for 3 h to obtain relatively stable CN or NV. 0.01-CN nanoparticle suspension. Then add 10 mL of CN or NV... 0.01 The deposition solution was obtained by uniformly mixing a CN nanoparticle suspension and 3 μL HI. Two 1×5 cm² areas were then prepared. 2 The FTO electrode was immersed in the deposition solution for 1 cm, and the FTO electrodes were placed parallel to each other at a distance of 1.5 cm. A voltage of 25 V was applied for 10 min for electrophoretic deposition to obtain CN / NV. 0.01 -CN electrode, tested after natural drying.

[0076] The prepared carbon nitride photoelectrode (CN / NV) 0.01 The working electrode was a platinum wire, the counter electrode was a platinum wire, and the reference electrode was an Ag / AgCl (saturated KCl) electrode. The buffer solution was a commercially available phosphate buffer solution (pH 7.4). The experiment was conducted in an aqueous solution containing K₂S₂O₈ (15 mM) as a co-reactant, KCl (0.1 M), and different concentrations of nitrite as electrolytes. Cyclic voltammetry was used for electrochemiluminescence testing, with an initial potential of 0 V, a termination potential of -1.5 V, and a scan rate of 100 mV / s. The photomultiplier tube voltage was set to 170 V to detect the electrochemiluminescence radiation signal.

[0077] like Figure 9 As shown, nitrite, a key component of fertilizers and food additives, is ubiquitous in the environment. Nitrite ions (NO2) - Excessive nitrite concentrations can have serious consequences for human health. Therefore, establishing a simple, flexible, and accurate method for nitrite detection is crucial. To address the issue of nitrite (NO2) concentrations... - As a public health and safety challenge posed by environmental pollutants, this invention is based on defect-engineered carbon nitride (NV). 0.01 -CN) constructed a novel electrochemiluminescence (ECL) biosensing platform, realizing NO2 - Ultrasensitive detection ( Figure 9 a). Its detection mechanism originates from NO2. - SO4 around the electrode ·- This leads to a decrease in ECL strength, such as Figure 9 As shown in a. With NO2 - The increase in CN and NV 0.01 -CN electrode cathode ECL signal gradually decreases ( Figure 9 b and Figure 9 c). For example Figure 9 As shown in d, NV 0.01 The logarithm of the ECL intensity of -CN and NO2 - The concentration exhibits excellent linearity, demonstrating a wider linear detection range (10) compared to sensing platforms built on CN. -13 Up to 10 -7M) and a lower detection limit (24.2 fM). Notably, due to the extremely high cathode ECL efficiency, the NV constructed in this invention... 0.01 -CN can be further developed into a visible cathode ECL biosensor, such as Figure 9 As shown in e.

Claims

1. A method for preparing high ECL-efficiency nitrogen-deficient functionalized carbon nitride, characterized in that, Includes the following steps: (1) Dissolve the carbon nitride precursor in an alkaline reagent by stirring, evaporate and dry the resulting solution overnight, grind it, and obtain a uniformly mixed sample; (2) The mixed sample was calcined in an inert gas atmosphere to obtain nitrogen-defect functionalized carbon nitride (NV). x -CN is the compound of formula (1).

2. The method for preparing high ECL-efficiency nitrogen-deficient functionalized carbon nitride in step (1) according to claim 1, characterized in that, The carbon nitride precursor is urea, and the alkaline reagent is KOH or NaOH.

3. The method for preparing high ECL-efficiency nitrogen-deficient functionalized carbon nitride in step (1) according to claim 1, characterized in that, The mass ratio of the carbon nitride precursor to the alkaline reagent is 5:0.002-0.

02.

4. The method for preparing high ECL-efficiency nitrogen-deficient functionalized carbon nitride in step (1) according to claim 1, characterized in that, The preferred mass ratio of the carbon nitride precursor to the alkaline reagent is 5:0.01-0.

02.

5. The method for preparing high ECL-efficiency nitrogen-deficient functionalized carbon nitride according to claim 4, characterized in that, The calcination in step (2) is carried out at a heating rate of 1-5℃ / min at 500-600℃ for 3-5 hours.

6. A high ECL-efficiency nitrogen-defect functionalized carbon nitride prepared by the preparation method of claim 1.

7. The high ECL-efficiency nitrogen-deficient functionalized carbon nitride according to claim 6, characterized in that, The high ECL-efficiency nitrogen-deficient functionalized carbon nitride at 2200 cm -1 Asymmetric tensile vibrations of -C≡N were observed at the location.

8. The high ECL-efficiency nitrogen-deficient functionalized carbon nitride according to claim 6, characterized in that, The high ECL-efficiency nitrogen-deficient functionalized carbon nitride possesses N vacancies (N... 2C ).

9. The application of the high ECL efficiency nitrogen-defect functionalized carbon nitride as described in claim 8 in the detection of electrochemiluminescence radiation signals and nitrite.

10. The application according to claim 9, characterized in that, The specific application process is as follows: using a nitrogen-deficient functionalized carbon nitride modified FTO electrode as the working electrode, a platinum wire electrode as the counter electrode, Ag / AgCl as the reference electrode, a phosphate buffer solution, and a KCl solution as the electrolyte; The electrodes were inserted into a buffer solution to perform an electrochemiluminescence test and detect the electrochemiluminescence radiation signal.